Legally speaking: navigating the legal landscape of digital investments - Abdul Manaf, Zati Ilham; Omoola, Sodiq (BERNAMA, 2023)
When considering digital asset investments, potential investors must pay attention to three key factors: legality, accessibility, and security. It is essential to familiarise oneself with the regulations in their jurisdiction, ensure that the investment is Syariah-compliant (if applicable), and take extra precautions to protect digital assets from potential security risks. Moreover, planning for after death is equally important, and investors can create a comprehensive digital estate plan to protect their digital assets and ensure that they are passed on to the intended beneficiaries. By taking these considerations into account, investors can make informed decisions and mitigate risks associated with digital asset investments.